Pengaruh Pertumbuhan Ekonomi Dan Pengangguran Terhadap Kemiskinan Di Provinsi Sumatera Selatan Pada Tahun 2019-2023 - Tini Febriani; Salman Allamsa; Widi Anggraeni; Muhammad Kurniawan (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
This research aims to determine the effect of economic growth and unemployment on poverty in South Sumatra Province in 2014-2023. This research uses a quantitative method which is a scientific approach to managerial and economic decision making. The analytical method used in this research is the multiple linear regression analysis method using an analysis tool, namely the Eviews 2010 program to facilitate data processing. The data used in this research is secondary data, secondary data was obtained from the Central Statistics Agency of South Sumatra Province for the period 2014 to 2023. The type of data used in this research is time series data, namely time series data. . The research results show 1) Economic Growth has an insignificant positive effect on Poverty. 2) Unemployment has an insignificant negative effect on poverty. 3) Economic Growth and Unemployment together have a positive and significant effect on Poverty.